2012
DOI: 10.1099/vir.0.037101-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of intracellular localization of PrPSc in prion-infected cells using a mAb that recognizes the region consisting of aa 119–127 of mouse PrP

Abstract: Generation of an abnormal isoform of the prion protein (PrPSc signals that were clustered at peri-nuclear regions appeared to be localized in an endocytic recycling compartment through which exogenously loaded transferrin, shiga and cholera toxin B subunits were transported. The granular PrP Sc signals at peri-nuclear regions were dispersed to the peripheral regions including the plasma membrane during incubation at 20 6C, at which temperature transport from the plasma membrane to peri-nuclear regions was impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
73
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(82 citation statements)
references
References 44 publications
(90 reference statements)
9
73
0
Order By: Relevance
“…This is consistent with previous reports by other investigators using other prion-infected cells 8,25 . Instead, most PrP Sc was observed throughout endosomal compartments, being particularly abundant in recycling endosome in infected cells.…”
Section: Articlesupporting
confidence: 94%
See 3 more Smart Citations
“…This is consistent with previous reports by other investigators using other prion-infected cells 8,25 . Instead, most PrP Sc was observed throughout endosomal compartments, being particularly abundant in recycling endosome in infected cells.…”
Section: Articlesupporting
confidence: 94%
“…Instead, most PrP Sc was observed throughout endosomal compartments, being particularly abundant in recycling endosome in infected cells. Similar subcellular distribution of PrP Sc was shown by others 25 . Accumulation of PrP Sc in recycling endosome was also shown in neurons of RML prion-infected mice 37 .…”
Section: Articlesupporting
confidence: 88%
See 2 more Smart Citations
“…Earlier studies suggested that PrP Sc is generated from mature PrP C expressed on the cell surface and that the PrP Sc generation occurs at cellular compartments on the endocytotic pathway, including the cholesterol-rich membrane microdomains called lipid rafts Naslavsky et al, 1997;Vey et al, 1996). Further cell biological studies within the following decade indicated the involvement of endocytic recycling compartments and endocytic recycling pathway in PrP Sc formation (Beranger et al, 2002;Marijanovic et al, 2009;Pimpinelli et al, 2005;Veith et al, 2009;Yamasaki et al, 2012). We recently reported that after the inoculation of prions, newly generated PrP Sc appeared on the cell surface, early endosomes, and late endosomes of N2a cells (Yamasaki et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%